Controllable Synthesis of Ultrathin NiCo2O4 Nanosheets Incorporated onto Composite Nanotubes for Efficient Oxygen Reduction. Issue 18 (15th August 2017) - Huang, Yunpeng; Cui, Fen; Zhao, Yan; Bao, Jian; Lian, Jiabiao; Xu, Yuanguo; Liu, Tianxi; Li, Huaming
Abstract: Exploring non‐precious‐metal‐based oxygen reduction reaction (ORR) electrocatalysts featuring high efficiency, low cost, and environmental friendliness is of great importance for the broad applications of fuel cells and metal–air batteries. In this work, ultrathin NiCo2 O4 nanosheets deposited on 1D SnO2 nanotubes (SNT) were successfully fabricated through a productive electrospinning technique followed by a sintering and low‐temperature coprecipitation strategy. This hierarchically engineered architecture has ultrathin NiCo2 O4 nanosheets uniformly and fully erected on both walls of tubular SNTs, which results in improved electrochemical activity as an ORR catalyst, in terms of positive onset potential and high current density, as well as superior tolerance to crossover effects and long‐term durability with respect to the commercial Pt/C catalyst. The excellent performance of SNT@NiCo2 O4 composites may originate from their rationally designed hierarchical tubular nanostructure with completely exposed active sites and interconnected 1D networks for efficient electron and electrolyte transfer; this makes these composite nanotubes promising candidates to replace platinum‐based catalysts for practical fuel cell and metal–air battery applications. Abstract : Creating composite catalysts : A nanocomposite of SnO2 nanotubes (SNTs) and ultrathin NiCo2 O4 nanosheets (SNT@NiCo2 O4 ) composed of perpendicularly oriented NiCo2 O4 nanosheets uniformly deposited on both walls of SnO2 nanotubes (see figure) has been synthesized. This nanocomposite can be used as a platinum‐free electrocatalyst for an efficient oxygen reduction reaction.